PUBLIC SECURITY AND COOPERATION BETWEEN STATE AND RELIGIOUS DENOMINATIONS - D’Arienzo, Maria (International Journal of Legal and Social Order, 2025)
The paper examines the collaboration between the State and religious denominations in Italy in the field of public security. It analyzes four key areas: the Catholic Church’s contribution to preventing mafia infiltration; the Holy See’s efforts to combat money laundering through alignment with international standards; the role of Islamic communities in countering terrorism and radicalization; and the reuse of places of worship as tools for integration and social cohesion. The study demonstrates that structured cooperation with religious actors strengthens legality, promotes intercultural dialogue, and supports preventive security policies, highlighting the strategic importance of these partnerships for collective safety and social resilience